Лікарська експертиза авіаційних фахівців - Галацан, О.В.; Люлько, О.М. (Актуальні проблеми транспортної медицини, 2009)
В статье дается анализ профессионально психологического отбора курсантов летного факультета. Впервые предложены новые организационные методы проведения медико психологи
ческой экспертизы летчиков, что окажет непосредственное влияние на повышение их профессиональной надежности. Рекомендовано привлечение специалиста в области психофизиоло
гии труда авиационного персонала в постоянный состав врачебно летных комиссий. In article the analysis has been done of professional and psychological selection of military students of pilot’s department. For the first time the new organization of medical and psychological expert examination of pilot’s are proposed, which will have the direct effects on the rise of their professional reliability. It is recommended to involve an expert in the field of aviation staff working psychology as a member of permanent medical commissions.